MOVING QUEER VISIBILITIES INTO IDENTITY-SUSTAINING PRACTICES IN CYC: TOWARD QUEER(ED) FUTURES - Longoria, A. (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
This essay aims at connecting child and youth care (CYC) to U.S. teacher education, educator pathways, and schooling in the United States. Further, this essay addresses Wolfgang Vachon’s call to push the boundaries of CYC, specifically in queering the field. I offer ways U.S. teacher education contexts and practices might be considered as guidance in supporting queer identities in CYC. I posit that there is a corporeal pedagogy that queer CYC practitioners enact that is effected beyond simple visibilities, and that they sustain their own identities and survival in CYC spaces through this practice. I also offer a testimonio of my practice as an out genderqueer, Chinese Mexican teacher educator who works in U.S. field-based teacher training and after-school CYC spaces. Further, I argue for critical engagement with curricula and field work in our training programs and make a call for training programs to support CYC practitioners in sustaining their queer identities. Finally, I argue for a need to continue to archive — and perhaps rescue — the practices and collective memories of queer CYC practitioners in order to advance a meaningful sustaining of queer identities in CYC.